The effects of zero tarriff on the textile industry based on the perspectives of ten of the top spinning mills - Gozum, Gladys G. M.; Florendo, Raquel Baltazar (1997.)
Through a descriptive documentary/survey among ten of the top textile spinning mills, this thesis tackled the different possible effects of zero tariffs and the problems which plague today's textile mills and keep them from being able to tap their potentials as bastions of industrialization. For the industry to survive radical trade reforms such as zero tariff and trade liberalization, it must decrease dependency on imported raw materials and improve its price and quality competitiveness during the span of time the different economic treaties have allotted for countries to prepare themselves. The sector will benefit greatly on the eradication of the age old problem of smuggling but its indirect and direct exports will suffer due to foreign competition. Consequently, the industry must concentrate on homing in on the local market. It must prepare itself for the folding up of old textile mills and be ready to make continuous improvements to be able to survive the price and quality war. This can be achieved if the industry makes improvements within itself: effective changes in management styles, production controls and product quality assurance in response to the problems of low productivity of workers, unionization and strikes, lack of trained personnel and lack of quality control standards and its implementation. It must link itself with allied industries to establish a local distribution network, develop new products and processes and gain government support as one cohesive sector. The government will be able to effectively assist the industry through careful policy-making to aid in the mills' acquisition of new machinery and equipment, the lowering of interest rates for borrowed funds, the revision of policies in the Board of Investments and implementation of less complicated customs procedures. Focus on necessary projects such a that of infrastructure and the peace and political stability of the country. It must also exert aggressive industry promotion and lastly, manifest more concern for environmental issues through pollution control.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Textile industry and fabrics